2008
DOI: 10.5352/jls.2008.18.10.1369
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Feeding Citrus by Products on Nutritional Components of Korean Native Chickens

Abstract: In this study, the effects of feeding citrus byproducts on nutritional components of Korean native chickens were investigated. Two samples of Korean native chickens were used for this study: T0 (chickens fed with only feed for laying hen until they became 39 weeks old, not with citrus byproducts) and T1 (chickens fed with citrus byproducts). The feed for T1 was the same as T0 for the first 16 weeks, and then was made by adding 4% of citrus byproducts to the feed for T0 between 17~39 weeks. The chicken used for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…It was reported that the content of highly unsaturated fat in meat was significantly increased when citrus pulp was added to the ostrich feed (Lanza et al, 2004). In addition, many studies have examined nutrition and quality after adding CJPW to livestock and bird feed (Yang et al, 2006;Jung et al, 2007;Yang et al, 2008). However, some studies have shown that CJPW promoted animal growth when used as a feed supplement, but other studies have found contrasting results (Bampidis and Robinson, 2006;Jwa and Yeo, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the content of highly unsaturated fat in meat was significantly increased when citrus pulp was added to the ostrich feed (Lanza et al, 2004). In addition, many studies have examined nutrition and quality after adding CJPW to livestock and bird feed (Yang et al, 2006;Jung et al, 2007;Yang et al, 2008). However, some studies have shown that CJPW promoted animal growth when used as a feed supplement, but other studies have found contrasting results (Bampidis and Robinson, 2006;Jwa and Yeo, 2015).…”
Section: Introductionmentioning
confidence: 99%